Serratus posterior superior intercostal plane block for breast surgery: A report of three cases, novel block and new indication - Çiftçi, Bahadır; Alver, Selçuk; Ahıskalıoğlu, Ali; Bilal, Bora; Tulgar, Serkan (Edizioni Minerva Medica, 2023)
Breast surgery is a common surgical procedure in the world. Since it affects the postoperative recovery and mobilization, pain after breast surgery is an important issue.1 Several regional techniques such as interpectoral/ pectoserratus blocks (PECS I/II), erector spinae plane block (ESPB), and rhomboid intercostal plane block (RIB) are used for pain relief after breast surgery. PECS I-II blocks most commonly used techniques for breast analgesia.2 However, they are closed to the surgical area, and the local anesthetic distribution may be affected by the surgical incision of the pectoral muscles. ESPB may be performed from the cervical to the sacral vertebrae. The clinical, cadaveric, and radiological results of ESPB are inconsistent.3 RIB provides focused hemithoracic analgesia; however, RIB fails to cover the cranial aspect of the T2 dermatome.4
Keywords: Breast Surgery; Superior Intercostal; New Indication